MOTIVASI KUNJUNGAN WISATAWAN TAMAN HUTAN RAYA SULTAN SYARIF HASYIM PEKANBARU RIAU - Purba, Christy Ulina; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research is to find out the motives and the motivators that influencedtourist to visit Forest park Sultan Syarif Hasim II.This research is uses descriptive quantitative methods to analyze problemwhich is going to conducted. The sample of this research was 100 people weretaken by using accidental sampling. Then the data collection techniques in this isreseach the writer used observation, interview and quisionnaires. The writerusing the likers scale as an instrument to measuring the lenght of intervals thatcan be used to find quantitative date.Based on the result of the research are the influence of motivator is moremotivate tourists to visit Forest park Sultan Syarif Hasim II than the motives.And, according to responden the motivation of tourists to visiting Forest parkSultan Syarif Hasim II is enough.Keyword: motivasi, motif dan motivator, pengunjung